2008
DOI: 10.1007/s12034-008-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Microwave dielectric properties of nanostructured nickel ferrite

Abstract: Nickel ferrite is one of the important ferrites used in microwave devices. In the present work, we have synthesized nanoparticles of nickel ferrite using chemical precipitation technique. The crystal structure and grain size of the particles are studied using XRD. The microwave dielectric properties of nanostructured nickel ferrite samples of three different average grain sizes and those of two sintered samples were studied. The parameters like dielectric constant, dielectric loss and heating coefficient of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…This may be due to the high density of samples which attributed to the defect free materials. Microwave dielectric properties of nanostructured nickel ferrite were done by Jacob et.al [40], in comparison with our results, loss tangent of the nick ferrite [40] is lower than Ni-Mg ferrite. It can be concluded that Mg doping improves loss tangent which cause to better microwave absorption.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 86%
“…This may be due to the high density of samples which attributed to the defect free materials. Microwave dielectric properties of nanostructured nickel ferrite were done by Jacob et.al [40], in comparison with our results, loss tangent of the nick ferrite [40] is lower than Ni-Mg ferrite. It can be concluded that Mg doping improves loss tangent which cause to better microwave absorption.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 86%
“…It may be seen that tand initially increases gradually, becomes maximum at a certain frequency and then starts decreasing with increase in frequency. This behaviour is similar to that reported by Jacob et al [8] The appearance of a resonance peak can be explained in a way that if an ion has more than one equilibrium position, say two positions A and B of equal potential energies separated by the potential barrier, the probabilities of jumping of ions from A to B and from B to A are the same. Depending upon this probability, the ion exchanges position between the two states with some frequency, called the natural frequency of jump between the two positions.…”
Section: Dielectric Properties Dielectric Constantsupporting
confidence: 89%
“…In ferrites with spinel structure having a structural formula, Fe 3þ [Mn 2þ Zn 2þ Fe 3þ ]O 4 , Mn 2þ and Zn 2þ together with half of the iron ions (Fe 3þ ) occupy the B site and the remaining half of the iron ions reside in the A site. The presence of Mn 2þ eMn 3þ and Zn 2þ eZn 3þ gives rise to the p-type carriers (holes) whereas Fe 2þ , Fe 3þ Sm 3þ and Gd 3þ ions produce n-type carriers (electrons) [32]. Therefore, both the electrons and holes that are present in the B sites are due to the presence of the Mn, Zn, Fe, Sm and Gd ions.…”
Section: Dielectric Propertiesmentioning
confidence: 99%